Pig and poultry farms as self-regulated biotechnology systems - a fundamental approach to environmental preservation - Grupče, Ljupčo (Macedonian Journal of Ecology and Environment, 1994)
The article is focused on the structural organization of pig and poultry farms as self-regulated biotechnology systems (BTS) in which a psichrophylic anaerobic system with three lagoons for utilization of the organic waste material is introduced. In this way the farms can simulate an organization of an ecosystem in which an easy flow of matter and energy is obtained. Due to that the BTS have high effects in environmental preservation and enable much more efficient utilization of the energy that enters the system.